Current research trends on the use of artificial intelligence in human capital management in organizations in the period 2018 - 2023 - Chávez De La Vega, Verónica Patricia; Rojas Rivera, Diego; Castro Ventura, Allison Sharon; Mendieta Flores, Victor Alberto; Paredes Delgado, Leonardo Luis; Larios Soldevilla, Omar Alexis; Moscoso Cuaresma, Julio Ricardo (LACCEI, 2023)
The objective of the research is to analyze and report the relationship and impact of the use of artificial intelligence in the management of human capital in organizations in the period 2018-2023. Artificial intelligence is in a process of evolution and is constantly present in today’s world. Artificial intelligence (AI) is defined as the execution and performance of tasks with a quality structure, which would also be performed by a human. With the results obtained about artificial intelligence, it gives us a clearer picture of the impact of the use of AI in companies in which it can replace and/or enhance human capital. However, based on the investigation, it is stated that the data obtained in the face of a possible replacement of the AI in the functions and tasks carried out by the human being are replaced in their entirety, it could be said that it will not materialize as such, but it will. improvements will be obtained in the efficiency of the tasks and objectives established by the organizations. Likewise, today’s world shows great interest in the application of AI, due to the great support that this will mean. Also, in the research it provides data which can be justified in the short or long term, highlighting that AI are sciences that seek to create highly capable technology for an innovative world.